2017
DOI: 10.5114/cipp.2018.72200
|View full text |Cite
|
Sign up to set email alerts
|

The need for power, need for influence, sense of power, and directiveness in female and male superiors and subordinates

Abstract: The purpose of the study was to examine the phenomenon of power within an organisation from the vantage point of gender, the occupied position, earnings, and the number of subordinates. participants and procedure The sample group comprised 107 female and 98 male participants. The mean age was 42.14 years (SD = 11.73).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A desire to influence has been identified as important motivators for both male and female leaders in a range of occupations, 48 as well as veterinary 28 . This was reiterated by the women in this study, in terms of having the control to make a positive change.…”
Section: Discussionmentioning
confidence: 57%
“…A desire to influence has been identified as important motivators for both male and female leaders in a range of occupations, 48 as well as veterinary 28 . This was reiterated by the women in this study, in terms of having the control to make a positive change.…”
Section: Discussionmentioning
confidence: 57%
“…Fewer studies have concentrated on the importance of the frontline managers' emotional exhaustion. As key personnel in organizations, frontline managers have more resources and power, and a greater sense of power compared to their subordinates [19,93]. However, there has been less research about how the sense of power affects emotional exhaustion.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Given that the core of leadership, across forms and styles, involves the influence of others (Zaleznik, 1977), power values are a central motivational factor underlying leadership. Accordingly, in many studies, the need for power has been shown to characterize effective leaders (e.g., Kocur & Mandal, 2018;McClelland & Boyatzis, 1982).…”
Section: The Motivational Contrast Of Power and Benevolencementioning
confidence: 99%
“…Given that the core of leadership, across forms and styles, involves the influence of others (Zaleznik, 1977), power values are a central motivational factor underlying leadership. Accordingly, in many studies, the need for power has been shown to characterize effective leaders (e.g., Kocur & Mandal, 2018; McClelland & Boyatzis, 1982). Left unchecked, however, power values may result in antisocial behavior, such as aggression (e.g., Knafo et al, 2008) and disagreeableness (e.g., Cheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%